Fate of recently assimilated carbon in the soil–plant system of Vaccinium vitis-idaea and its response to warming in a 2.5-year translocation experiment - Valentin B. Kurbel; Outi-Maaria Sietiö; Kristiina Karhu; Andrei Rodionov; Sari Timonen; Thomas Ohnemus; Eva Lehndorff; Johanna Pausch; Nele Meyer (Plant and Soil, 2026)
Background and aims Shrubs like Vaccinium vitis-idaea substantially contribute to forest carbon (C) sequestration. Therefore, understanding their allocation patterns under climate change is crucial. We conducted a translocation experiment with 13 CO 2 pulse-labelling to test if (I) belowground pools accumulate total and recently assimilated C, (II) within fine roots, assimilated C is preferentially allocated to root tips and mycorrhized cells and (III), whether warming alters C allocation patterns. Methods We translocated soil cores with V. vitis-idaea from North- to South-Finland (+ 3.7 °C mean temperature). After 2.5 years, we excavated and pulse-labelled them with 13 CO 2 , tracing the 13 C in plant, soil, and respiration. We used laser-ablation isotope ratio mass spectrometry to examine 13 C distribution in fine roots. Results Roots represented the largest plant C pool (north: 49.69 ± 9.73%, translocated: 43.92 ± 6.59% of plant C stock). A substantial amount of recently assimilated 13 C was recovered belowground (roots + soil, north: 15.59 ± 5.77%, translocated: 39.21 ± 29.32%) 8 days after labelling. Most assimilated C was respired (north: 63.3 ± 5.9%, translocated: 44.1 ± 3.2%) or recovered in leaves (north: 17.9 ± 5.92%, translocated: 19.2 ± 3.19%). Within fine roots, 13 C content tended to be higher at root tips, while mycorrhizal infection had no effect. Warming tended to increase C allocation to the shoot and significantly decreased 13 C in the microbial biomass in the mineral soil. Conclusion V. vitis-idaea allocates a large portion of assimilates belowground, but 2.5 years of warming only marginally change C allocation patterns. Accelerated soil microbial processes after translocation may increase plant N availability, potentially affecting C allocation over longer time spans.

Improving runoff quality in vertical greenery systems: Substrate type outweighed the effect of plant growth promoting microbes - Xi Shu; D. Johan Kotze; Sari Timonen; Susanna Lehvävirta; Long Xie (Science of The Total Environment, 2023)

Arbuscular mycorrhizal symbioses in a cut-and-carry forage production system of legume tree Gliricidia sepium and fodder grass Dichanthium aristatum - Riina Jalonen; Sari Timonen; Jorge Sierra; Pekka Nygren (Agroforestry Systems, 2013)

Cerebellar Glucose During Fasting and Acute Hyperglycemia in Nondiabetic Men and in Men with Type 1 Diabetes - Outi Heikkilä; Sari Mäkimattila; Marjut Timonen; Per-Henrik Groop; Sami Heikkinen; Nina Lundbom (The Cerebellum, 2010)

Evidence for abnormal glucose uptake or metabolism in thalamus during acute hyperglycaemia in type 1 diabetes—a 1H MRS study - Outi Heikkilä; Nina Lundbom; Marjut Timonen; Per-Henrik Groop; Sami Heikkinen; Sari Mäkimattila (Metabolic Brain Disease, 2010)

Effects of sugar beet chitinase IV on root-associated fungal community of transgenic silver birch in a field trial - Hanna-Leena Pasonen; Jinrong Lu; Anna-Maija Niskanen; Sanna-Kaisa Seppänen; Anna Rytkönen; Janne Raunio; Ari Pappinen; Risto Kasanen; Sari Timonen (Planta, 2009)

Archaea in dry soil environments - Sari Timonen; Malin Bomberg (Phytochemistry Reviews, 2009)

Risk for metabolic syndrome predisposes to alterations in the thalamic metabolism - Outi Heikkilä; Nina Lundbom; Marjut Timonen; Per-Henrik Groop; Sami Heikkinen; Sari Mäkimattila (Metabolic Brain Disease, 2008)

Cytoskeleton in mycorrhizal symbiosis - Sari Timonen; R. Larry Peterson (Plant and Soil, 2002)

ITS rDNA sequence-based phylogenetic analysis of Tomentellopsis species from boreal and temperate forests, and the identification of pink-type ectomycorrhizas - Urmas Kõljalg; Hanna Tammi; Sari Timonen; Reinhard Agerer; Robin Sen (Mycological Progress, 2002)